Transcriptional Regulation of Aluminum-Tolerance Genes in Higher Plants: Clarifying the Underlying Molecular Mechanisms - Daspute, Abhijit A.; Sadhukhan, Ayan; Tokizawa, Mutsutomo; Kobayashi, Yuriko; Panda, Sanjib K.; Koyama, Hiroyuki (Frontiers in Plant Science, 2017)
Aluminum (Al) rhizotoxicity is one of the major environmental stresses that decrease global food production. Clarifying the molecular mechanisms underlying Al tolerance may contribute to the breeding of Al-tolerant crops. Recent studies identified various Al-tolerance genes. The expression of these genes is inducible by Al. Studies of the major Arabidopsis thaliana Al-tolerance gene, ARABIDOPSIS THALIANA ALUMINUM-ACTIVATED MALATE TRANSPORTER 1 (AtALMT1), which encodes an Al-activated malate transporter, revealed that the Al-inducible expression is regulated by a SENSITIVE TO PROTON RHIXOTOXICITY 1 (STOP1) zinc-finger transcription factor. This system, which involves STOP1 and organic acid transporters, is conserved in diverse plant species. The expression of AtALMT1 is also upregulated by several phytohormones and hydrogen peroxide, suggesting there is crosstalk among the signals involved in the transcriptional regulation of AtALMT1. Additionally, phytohormones and reactive oxygen species (ROS) activate various transcriptional responses, including the expression of genes related to increased Al tolerance or the suppression of root growth under Al stress conditions. For example, Al suppressed root growth due to abnormal accumulation of auxin and cytokinin. It activates transcription of TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS 1 and other phytohormone responsive genes in distal transition zone, which causes suppression of root elongation. On the other hand, overexpression of Al inducible genes for ROS-detoxifying enzymes such as GLUTATHIONE–S-TRANSFERASE, PEROXIDASE, SUPEROXIDE DISMUTASE enhances Al resistance in several plant species. We herein summarize the complex transcriptional regulation of Al-inducible genes affected by STOP1, phytohormones, and reactive oxygen species.